PERANCANGAN APLIKASI PENJUALAN ONLINE UNTUK MENINGKATKAN OMSET PENJUALAN (STUDI KASUS : BUTIK CHANIAGO JAMBI): Butik Chaniago Jambi;Ecommerce;MySql;Promosi;Web Profil. - Lisdarti; Hidayat, Rohmat (FORTECH (Journal of Information Technology), 2022)
The limited reach of the marketing of goods and the lack of efficiency of the product promotion system to the public have caused the maximum turnover of the Chaniago Jambi boutique not to be achieved. The rapid development of internet technology at this time can support the application of a web profile system and promotion in product sales at the Chaniago Jambi boutique. The purpose of this research is to create a web profile and promotion at the Chaniago boutique, which is used for media promotion and product marketing via the internet. The method used is to conduct a literature study on the profi web work system, then design the design and work profile web system, which is then implemented by making this profile and promotion web. The conclusion obtained is that this web profile has been successfully created using the PHP programming language combined with the MySql database. The advantage of this system is that the promotions carried out at this chaniago boutique are able to save time and costs, compared to promotions that are done manually or using banners. And with this web profile and promotion system, it can help the Boutique, in handling the promotion and marketing system more effectively and efficiently.